(untitled) (World Bulletin of Social Sciences, 2024)
This study aims to analyze environmental justice as a reflection of the issue of social justice. The authors analyzed the term “environmental justice,” which is directly related to “social justice.” The basis of environmental justice is the principles of a social organization projected onto the interaction between people and the environment